The Dark Past of Slavery in American Plantation Houses: Website Promotion and Perceptions of Visitors in TripAdvisor Reviews - Cavalieri, Silvia; Corrizzato, Sara; Franceschi, Valeria (Collection of Papers of the Faculty of Philosophy in Priština, 2022)
The visual and linguistic representations of tourism destinations for promotional aims may be affected by their primary function of acquiring new visitors; for this reason, they are not always “value-free expressions of a place’s identity” (Pritchard & Morgan, 2001, p. 177). The concept of dark tourism seems to perfectly mirror the connection between terminological choices and culturally-bound constraints. It has been acknowledged that several dark tourism sites tend to valorise (or hide) events associated with tragedy and death, attracting tourists’ interest for their (non)macabre details at the expense of historical objectivity. This is the case of plantation houses in the US, whose narrative on slavery has often been “whitewashed” and minimized (e.g., Harnay, 2022; Butler, 2001; Eichstedt & Small, 2002). This study aims at investigating how visitors to popular plantation destinations in the US perceive and evaluate the presentation of the experience of slavery in these sites vis-à-vis what is presented on the plantation websites. The analysis is therefore twofold: first, a qualitative multimodal study of the content included in the websites of the plantations will shed light on whether the websites include information on the role of slave labour in the plantations, and secondly, a corpus-assisted investigation of the visitors’ reviews posted on TripAdvisor will attempt to clarify how visitors perceive the plantations as a tourist location, and the importance they place on receiving honest information about the brutality of slavery during their visits. The mixed-methods approach has allowed researchers to delve into this phenomenon from two opposite, but intertwined, perspectives: one driven by experts officially promoting the visit through the websites and the other offered by visitors sharing their personal experiences and feelings.
Keywords: corpus linguistics; dark tourism; plantation houses; TripAdvisor; slavery